Organisational culture and the millennials' intention to stay: the mediating role of leadership management practices - Islam, Md Asadul; Jantan, Amer Hamzah; Hashim, Haslinda; Choo, Wei Chong (InderScience, 2022)
This study aims to examine the mediating role of leadership practices of managers in relation to organisational culture (supportive and innovative) and intention to stay. The study utilised the quantitative methodology for which a structured questionnaire was developed to collect data from 300 millennial employees working in the RMG industry in Bangladesh. Collected data were analysed using the partial least squares structural equation modelling. Analysis of the study reveal that leadership practices of managers and organisational supportive culture have a significant impact on the intention to stay of millennials whilst the organisational innovative culture does not have a significant impact on the intention to stay. Furthermore, the results show that the organisational culture has a significant impact on the organisational leadership practices of managers. The study also finds the mediating role of leadership practices of managers in relation to organisational culture and intention to stay. Implications, limitations and future research directions are discussed.